Animosity within borders: The mediating roles of regional identification and perceived discrimination on regional media preference. Issue 5 (9th November 2015) - Huang, Yu-An; Lin, Chad; Yen, Dorothy A
Abstract : Purpose: – The purpose of this paper is to identify and examine the antecedents and consequence of regional animosity and their impacts on regional media preference. Design/methodology/approach: – Computer-assisted telephone interviews were conducted with randomly selected adult residents in Northern (206) and Southern (201) Taiwan. The data were analyzed using structural equation modeling in LISERAL and fuzzy-set qualitative comparative analysis. Findings: – The findings reveal that perceived economic threat, economic hardship and dissatisfaction with government economic policy increase home region identification and perceived discrimination, which in turn lead to heightened animosity toward the opposite foreign region. This increasing animosity then affects consumer choice over home region media compared to media originated from the other region. Research limitations/implications: – The findings suggest that military and political tensions alone cannot explain why consumers would harbor animosity between one region and another within the same country due to social and economic reasons. The constructs chosen in this research should be seen only as a snapshot but other variables such as a region's natural environment and its human factors are not taken into account. Future studies would benefit from inclusion of these variables and a wider geographical scope. Practical implications: – Several implications are extracted to help marketing and branding personnel better shape their marketing, communication and media strategies, as well as to help government policy makers and political parties revise existing policy to reduce the animosity. Originality/value: – By investigating animosity within borders, this study provides fresh insights to help explain how economic factors contribute to increased regional animosity through the mediating effect of regional identification and perceived discrimination. The findings broaden existing understanding about the concept of animosity and its impact on consumer behavior.